2021
DOI: 10.5194/acp-21-16027-2021
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of combustion Fe in marine aerosols over the northwestern Pacific estimated by Fe stable isotope ratios

Abstract: Abstract. The source apportionment of aerosol iron (Fe), including natural and combustion Fe, is an important issue because aerosol Fe can enhance oceanic primary production in the surface ocean. Based on our previous finding that combustion Fe emitted by evaporation processes has Fe isotope ratios (δ56Fe) that are approximately 4 ‰ lower than those of natural Fe, this study aimed to distinguish aerosol Fe sources over the northwestern Pacific using two size-fractionated marine aerosols. The δ56Fe values of fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 100 publications
5
44
0
Order By: Relevance
“…The enrichments of labile Fe and Al in fine fractions have been reported by previous studies (Baker and Jickells, 2006; Fe in fine fractions is the presence of pyrogenic Fe in fine fractions (Kurisu et al, 2021). Oil combustions, including ship emissions, are one of the dominant sources of pyrogenic Fe in fine aerosol particles because several studies have been reported…”
Section: Size Distributions Of Fe and Al Concentrationsmentioning
confidence: 73%
See 2 more Smart Citations
“…The enrichments of labile Fe and Al in fine fractions have been reported by previous studies (Baker and Jickells, 2006; Fe in fine fractions is the presence of pyrogenic Fe in fine fractions (Kurisu et al, 2021). Oil combustions, including ship emissions, are one of the dominant sources of pyrogenic Fe in fine aerosol particles because several studies have been reported…”
Section: Size Distributions Of Fe and Al Concentrationsmentioning
confidence: 73%
“…However, fractional Fe solubility (Fesol% = (labile Fe/total Fe) × 100) in mineral dust in source regions is usually less than 1.0% because Fe in mineral dust is typically present as insoluble species (e.g., Fe in aluminosilicates and Fe (hydr)oxides). In contrast, a wide range of Fesol% in marine aerosol particles (0.1-90%) has been reported by previous observational studies (Buck et al, 2006;2013, Baker andJickells, 2006;Bakers et al, 2016Bakers et al, , 2021Chance et al, 2015;Kurisu et al, 2021). One of the reasons for high Fesol% in the marine aerosol particles is pyrogenic Fe with high Fesol% (up to 80%, Schroth et al, 2009;Takahashi et al, 2013;Kurisu et al, 2016;Conway et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, a wide range of Fe sol % in marine aerosol particles (0.1 %-90 %) has been reported in previous observational studies (Buck et al, 2006(Buck et al, , 2010(Buck et al, , 2013Baker and Jickells, 2006;Bakers et al, 2016Bakers et al, , 2021Chance et al, 2015;Shelley et al, 2018;Kurisu et al, 2021). One of the reasons for the high Fe sol % in marine aerosol particles is pyrogenic Fe with high Fe sol % (up to 80 %, Schroth et al, 2009;Takahashi et al, 2013;Kurisu et al, 2016Kurisu et al, , 2019Kurisu et al, , 2021Conway et al, 2019). It seems that the variation in Fe sol % in marine aerosol particles can be explained by a binary mixing system of mineral dust and anthropogenic aerosols if the Fe sol % of these components at the time of emission is known.…”
Section: Introductionmentioning
confidence: 84%
“…However, fractional Fe solubility (Fe sol % = (labile Fe / total Fe) × 100) in mineral dust in source regions is usually below 1.0 % because Fe in mineral dust is typically present as insoluble species, e.g., Fe in aluminosilicates and Fe (hydr)oxides. In contrast, a wide range of Fe sol % in marine aerosol particles (0.1 %-90 %) has been reported in previous observational studies (Buck et al, 2006(Buck et al, , 2010(Buck et al, , 2013Baker and Jickells, 2006;Bakers et al, 2016Bakers et al, , 2021Chance et al, 2015;Shelley et al, 2018;Kurisu et al, 2021). One of the reasons for the high Fe sol % in marine aerosol particles is pyrogenic Fe with high Fe sol % (up to 80 %, Schroth et al, 2009;Takahashi et al, 2013;Kurisu et al, 2016Kurisu et al, , 2019Kurisu et al, , 2021Conway et al, 2019).…”
Section: Introductionmentioning
confidence: 89%